Alih Aksara dan Alih Bahasa Teks Hikayat Maulud Nabi - Fadilla Destikayana Tasri; Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to present the form of a physical description of the Hikayat Maulud Nabi text, present the form of transliteration of the Hikayat Maulud Nabi text, and present the form of the translation of the Hikayat Maulud Nabi text. The object of this research is manuscript and text of Hikayat Maulud Nabi. The method used is the philological method which consists of several stages of research. At the data collection stage, the literature study method was used, at the script description stage at descriptive method was used, at the transliteration stage the translation method used, and at the language transfer stage the translation method used. The results of this study are threefold, namely (a) the form of the description of the Hikayat Maulud Nabi manuscript which is described based on the things that have been determined in describing or identifying the manuscript; (b) the presentation of the transliterated form of the Hikayat Maulud Nabi text. Transliteration is done from Arabic-Malay script to Latin script; (c) presentation of the translated form of the text Hikayat Maulud Nabi being translated from Malay to Indonesia. Hikayat Maulud Nabi manuscript contains the history of the birth of the Prophet Muhammad.